Study of priming effects on some phonological and seed germination characteristics and of two hybrid Maize (Zea mays L. CV. Single cross 704 and 640)in delayed summer cropping of Mazandaran provience - احمد محسنی; رضا رضایی سوخت آبندانی; مهدی رمضانی (علوم و فناوری بذر ایران)
This study did with the aim of investigating osmopriming effect on phonological characteristics and some germination features in hybrid Maize (Zea mays L. CV. Single cross 704 and 640). This was carried out with a factorial experiment in randomized completely block design with tree on four replications, in seeds field and lab research which performed in Mazandaran naturon resources and cultivation, modification plants group, 2010-2011 mordad, respectively. Treatments included seed of two kind maize (640 and 704) and seven polyethilen glycol solution with 5 and 10 percent densities, potassium nitrat with 0.5 and 1 percent densities and choloride potassium with 1 and 2 densities, water and control (with out priming). Seedling emergence percent, Seedling emergence rate , Established seedlings, Day number sowing to rise coleoptiles, Day number sowing to stage 4 and 8 leaf, Day number to emergence tasel, Day number to the end of milk stage achieved, Germination percent, Germination rate, Normal seedlings number, Mean daily germination,Germination rate indx, Mean time to germination and Vigor 2 index.However, none of characteristics from statistican point under numbers in fluence showed meaningful difference, but results indicated that more percent and maize dermination rate achieved respectively with priming by polyethilen glycol solution with 5 and 10 percent densities. Which, most established seedlings to rise coleoptile, days number sowing to stage 4 and 8 leaf, days number to emergence tasel resulted with priming by control (with out priming) and their lowest was for polyethilen glycol with 5 and 10 percent respectively. Also, most of days number to the end of milk stage achieved with priming by potassium nitrate and choloride with 0.5 1 and 2 percent respectively. Most percend and germination rate for hydropriming and control (with out priming) and most normal seedling number and mean daily germination for water and control were obtained. Maximum of germination rate index and mean daily germination for control prime (with out priming) and minimum of mean germination time with priming by potassium nitrat and choloride with 0.5 and 4 percent obtained and also maximum of vigour 2 index for hydropriming and it ,s minimum was achieved for potassium nitrate and cholorid priming solution with0.5 and 4 percent resulted. Hence, both field and lab situations statistically were not under interaction effect on variety andtimes; priming and they havenandrsquo;t meaningful difference.